Efektivitas Gel Madu Hutan Akasia terhadap Jumlah Fibroblas pada Luka Sayat Tikus Putih (Rattus novergicus) - Bimby Irenesia; puan sadila islami; riski dwi utami (Indonesian Journal of Pharmaceutical Education, 2023)
Cuts are wounds caused by sharp objects such as knives, swords, razors and glass. According to data from the Arifin Achmad Regional General Hospital, Riau Province, it was noted that the most common type of wound in sharp violence was a cut (66.7%). When a wound occurs, the wound healing process occurs, namely: inflammation, proliferation, and remodeling. During the proliferative phase, fibroblasts influence the reepithelialization process that closes the wound. Handling cuts using acacia honey because acacia honey in wound healing has anti-inflammatory, antibacterial and antioxidant activities. Knowing the effectiveness of acacia honey gel on the number of fibroblasts in white rat (Rattus novergicus) incision wounds. This type of research is an experimental study design with a randomized posttest only control group design that uses acacia honey on cuts in white rats (Rattus novergicus). There was no significant difference between each treatment group: 20% acacia honey gel, 60% acacia honey gel, 80% acacia honey gel, positive control (povidone iodine) and negative control (gel without honey). Giving acacia honey gel could not increase the number of fibroblasts in white rat (Rattus novergicus) incision wounds.